Corticomedullary Index of Human Kidney - Hassan, SM Nurul; Nargis, Waheeda; Khalil, Mansur; Khalil, Mohsin; Alam, Md. Rafiqul (Bangladesh Journal of Anatomy, 2013)
Bangladesh Journal of Anatomy, January 2012, Vol. 10 No. 1 pp 20-22 DOI: http://dx.doi.org/10.3329/bja.v10i1.15753